Case Review of Impacted Bile Duct Stone at Duodenal Papilla: Detection and Endoscopic Treatment - Joo, Kwang Ro (Yonsei University College of Medicine, 2010)
PURPOSE: A bile duct stone impacted at the duodenal papilla is an urgent condition that can rapidly lead to either suppurative cholangitis or acute pancreatitis due to almost complete obstruction of the bilio-pancreatic outflow. This study evaluated the clinical characteristics and results of endoscopic treatment for a bile duct stone impacted at the duodenal papilla. MATERIALS AND METHODS: Forty-six patients who had been diagnosed with an impacted papillary stone were retrospectively reviewed. RESULTS: The typical features of acute cholangitis (Charcot's triad) and pancreatitis were only observed only in 10 patients (21.7%) and 17 patients (37.0%), respectively. After the endoscopic retrograde cholangiopancreatography, 30 patients (65.2%) were found to have a solitary stone impacting the duodenal papilla and 16 patients had one or more stones in the bile duct. On the radiological studies, the former patients were associated more commonly with no visible stone or no bile duct dilatation (p < 0.05). All impacted papillary stones were successfully removed by endoscopic sphincterotomy: 23 by a needle knife and 23 by a pull type papillotome. The procedure-related complications (n = 7, 4 bleeding, 3 pancreatitis) were not serious and did not differ, based on endoscopic findings and the procedure used. CONCLUSION: A bile duct stone impacted at the duodenal papilla requires both clinical and radiographic evidence to support the diagnosis. Endoscopic sphincterotomy, either with a needle knife or a pull type papillotome, was safe and effective for removing the impacted papillary stone.